ATTITUDES TOWARDS AUTISTIC SPECTRUM DISORDER: A SYSTEMATIC REVIEW: atitudes frente ao transtorno do espectro autista: revisão sistemática - Mírian Carvalho,; Luiz Fernando de Oliveira Santos,; Andrêsa Fernanda Gomes Pereira,; Suiane Magalhães Tavares,; Carlos Eduardo Pimentel, (Revista de Ciências da Saúde Nova Esperança, 2025)
The Autistic Spectrum Disorder incorporates a variety of serious disorders in the way individuals interact and communicate. Considering the relevance of social relationships in the treatment of autism, this study aimed to analyze the research instruments used to verify the attitudes of the population against the autistic spectrum disorder, aiming to understand people's thoughts, feelings and behaviors against individuals with this condition. This systematic literature review was conducted using the Prisma Protocol, with the CAPES and Pubmed databases, the descriptors were verified in the Decs (Health Sciences Descriptors)/Mesh (Medical Subject Headings) and BVS PSI (Virtual Health Library - Psychology Brazil), being used the following unitmates: "Autism Spectrum Disorder” and "Attitude" and "Instruments". Seven articles were analyzed, of which the following instruments were observed: Lifespan Sibling Relationship Scale; J-mas, translation of the multidimensional attitudes scale) to Japanese; Likert method (explicit attitudes); ST -iat method (implicit attitudes); Adjective Verification List (ACL); Parental Attitude Research Instrument; Parental Attitudes Questionnaire; Questionnaire on attitudes and pedagogical practices for people with ASD, based on the universal design of Rose's learning (2003); and Behavior Guidance Techniques. The main attitudes identified included: Mother's Dominance attitude, family dependence attitude, attitude of superauthority, positive siblings' attitudes in adolescence and positive cognitive and behavioral attitudes after interaction with people with autism. Thus, it is understood the relevance and importance of the present work in the dissemination and reflection on the theme, as in the use of future research, aiming to broaden the understanding of the factors that influence social perception and everyday interactions, about people diagnosed with autism.